Accessing the Hotspots of Cavity Plasmon Modes in Vertical Metal–Insulator–Metal Structures for Surface Enhanced Raman Scattering. Issue 7 (4th February 2020) - Dai, Fang; Horrer, Andreas; Adam, Pierre‐Michel; Fleischer, Monika
Abstract: In metal–insulator–metal structures such as Au nanodiscs on an Au film separated by a thin oxide spacer layer, the metal/insulator interfaces can form a Fabry–Perot cavity in which gap surface plasmons are confined. As a result, these cavity plasmon modes show the advantageous properties of strong field enhancement and very narrow resonance line shapes due to the confinement in a cavity. In this work, the hotspots of the electromagnetic near‐field of cavity plasmon modes are exposed to make the strongly enhanced field accessible to Raman molecules. This is achieved by creating an undercut in the spacer between the Au discs and the gold film by wet etching of the spacer. The electromagnetic field distributions as well as the resonance wavelengths of two different cavity plasmon modes in such cavities both with and without undercut are studied by simulations based on the finite element method. The size of the undercut is estimated by relating the measured spectral shift before and after reducing the spacer disc to the one obtained in simulations. Surface enhanced Raman scattering measurements are conducted on arrays of cavities. The effect of the undercut on the Raman scattering intensity is investigated and a notable increase is found. Abstract : Gold nanodisc arrays on a gold film separated by a thin insulator spacer enable strongly confined and enhanced near‐fields localized inside the spacer. An undercut in the spacer can expose the hotspots to the environment and lead to a strong increase of the surface enhanced Raman intensity.